SCoT Markers Analysis for Genetic Diversity in Indian Mustard (Brassica juncea L.) - Kumar, Amit; Verma, P. N.; Pandey, V. K.; Tyagi, Dev; Musa, Umar (International Journal of Bio-resource and Stress Management, 2026)
The present study was conducted during rabi (December, 2022–April, 2023) at the Integral Institute of Agricultural Science and Technology (IIAST), Integral University, Lucknow, India to assess genetic diversity among ten Indian mustard (Brassica juncea L.) genotypes using Start CodonTargeted (SCoT) markers. Ten SCoT primers were screened, and PCR amplification was performed using a programmable thermocycler (Prima-96, Hi-Media, India). The reaction mixture for SSR-PCR included 6 µl of DNA template (15 ng µl-1), 1 µl each of forward and reverse primers, 10 µl of 1X Hi-Chrome master mix, and 2 µl of double-distilled water, totaling 20 µl. High-quality DNA was used for amplification, and primers were selected based on banding patterns for further characterization. Polymorphism information content (PIC) values ranged from 0.26 to 0.37, with an average of 0.31. Primer 8(45) exhibited the highest PIC value (0.37), indicating its effectiveness in detecting genetic diversity, followed by Primer 5(42) and Primer 7(44) (both 0.35). The UPGMA dendrogram, generated using Primer SCoT37, revealed two major clusters: Cluster 1 (PM-31,Urwashi, Maya) and Cluster 2 (NDR8501, Varuna, NDYR-8, RH-749, Pitambari, Rohini, Azad-Mahak). PM-31 and Urwashi showed the closest genetic relationship (distance: 16.0), while Azad-Mahak was the most genetically distinct genotype (distance: 32.2). These findings highlighted the utility of SCoT markers in assessing genetic diversity and relationships among mustard genotypes, providing valuable insights for breeding programs and conservation genetics.